Knowledge sharing in Asia Pacific via virtual community platform: a systematic review. (10th October 2019) - Fauzi, Muhammad Ashraf
Virtual community (VC) is a platform for users to exchange knowledge for various purposes. Recent trends show that VC is highly anticipated in Asia Pacific regions. Using systematic review, this paper presents all VC studies in Asia Pacific region from the years 2006 to 2019, a 13-period. Outcome shows that VC studies primarily conducted in Taiwan, China and South Korea more than any other countries in the world, not only in Asia Pacific. Similar variables were identified in this region VC studies including trust, altruism, reciprocity and various other social factors. Several theories were also used in VC studies such as theory of planned behaviour, social capital theory, social cognitive theory, social exchange theory and social identity theory. Implication towards theoretical and managerial aspects is prominent in term of user's engagement in using the platform based on different countries engagement with VC.